Covid 19 Pandemic Mitigation in Indonesia - Zeffry Alkatiri (Journal of Indonesian Social Sciences and Humanities, 2021)
Reviewing Mas`udi, W. & Winanti., P. W. (2020). Tata Kelola Penanganan COVID-19 di Indonesia: Kajian Awal. Yogyakarta: Gajah Mada University Press.